2020
DOI: 10.4315/jfp-20-010
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Listeria monocytogenes in Ready-to-Eat Meat and Poultry Product Verification Testing Samples from U.S. Department of Agriculture–Regulated Producing Establishments, 2005 through 2017

Abstract: Ready-to-eat (RTE) meat and poultry product samples collected between 2005 and 2017 from RTE producing establishments for the Food Safety and Inspection Service’s (FSIS’s) ALLRTE/RTEPROD_RAND (random) and RTE001/RTEPROD_RISK (risk-based) sampling projects were tested for Listeria monocytogenes ( Lm ). Data for 45,897 ALLRTE/RTEPROD_RAND samples collected from 3607 unique establishments and 112,347 RTE001/RTEPROD_RISK samples collected from 3283 unique establishments were analyzed for the presence of Lm . These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 8 publications
(14 reference statements)
0
2
1
Order By: Relevance
“…However, this can be considered a low percentage compared with the results obtained in other similar studies, of 8.5 to 53.3% [ 57 , 62 , 63 , 64 , 65 , 66 , 67 ]. In contrast to the findings reported by Mamber et al [ 68 ], our results showed a higher percentage. In their study, 0.46% of chicken samples collected from the USA were tested positive for L. monocytogenes.…”
Section: Discussioncontrasting
confidence: 99%
“…However, this can be considered a low percentage compared with the results obtained in other similar studies, of 8.5 to 53.3% [ 57 , 62 , 63 , 64 , 65 , 66 , 67 ]. In contrast to the findings reported by Mamber et al [ 68 ], our results showed a higher percentage. In their study, 0.46% of chicken samples collected from the USA were tested positive for L. monocytogenes.…”
Section: Discussioncontrasting
confidence: 99%
“…Listeria monocytogenes is an ubiquitous Gram-positive bacterium able to contaminate a wide variety of foodstuffs; particularly, it is considered a relevant foodborne pathogen commonly associated with ready-to-eat (RTE) products [1,2]. The microorganism is responsible for numerous outbreaks of listeriosis worldwide [3][4][5][6] with high mortality rates in specific population categories such as immunocompromised subjects, elderly and pregnant women [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, meat and meat products are a suitable medium for growth of various pathogenic and spoilage microorganisms due to the presence of essential nutrients, absence of competing microorganisms, and desirable water activity and pH (Galvez et al, 2008). In addition, environments of food production and ingredients applied in the recipes of products such as frankfurters and sausages can facilitate microbial proliferation (Mamber et al, 2020). Therefore, meat and meat products must be produced and stored under safe and hygienic conditions.…”
Section: Introductionmentioning
confidence: 99%